Pedagogías emergentes y educación: Una revisión sistemática de estudios en REDALYC - León Toro Gisella Tatiana (My University, 2025)
This article presents a systematic literature review on emergent pedagogies in the educational field. The aim was to analyze the evolution of these new pedagogical approaches over the recent years (2020–2024). Based on information gathering, the research is founded on a review of 271 articles in the REDALYC database, of which 44 key texts were selected for a more in-depth analysis. This study, which uses a mixed methods approach with a qualitative–quantitative focus, seeks to understand how emergent pedagogies respond to the growing needs of today’s society, which encompass sociocultural, technological, and scientific aspects, and how these elements influence their implementation in educational institutions. On the other hand, evidence shows that emergent pedagogies promote participatory, flexible, and meaningful learning. Their approach centers on the individual student’s experience, as it fosters the autonomous and creative development of communication skills, enabling learners to analyze diverse contexts and confront real-world problems. It is worth noting that the texts reviewed identify several common thematic axes with perceptible changes in the establishment of these pedagogies, highlighting innovation, inclusion, and resilience as fundamental aspects in the educational field.
En este artículo se presenta una revisión sistemática de la literatura sobre las pedagogías emergentes en el ámbito educativo. El objetivo fue analizar la evolución de estos nuevos enfoques pedagógicos durante estos últimos años (2020-2024). De acuerdo con la recolección de información, la investigación se basa en una revisión de 271 artículos en la Base de Datos REDALYC, de los cuales se seleccionaron 44 textos claves para un análisis más profundo. Este estudio que utiliza un método mixto con enfoque cualitativo – cuantitativo, busca comprender como las pedagogías emergentes responden a las crecientes necesidades de la sociedad actual, las cuales abarcan aspectos socioculturales, tecnológicos y científicos; y cómo estos elementos influyen en su implementación en las instituciones educativas. Por otro lado, evidencia como las pedagogías emergentes promueven un aprendizaje participativo, flexible y significativo. Su enfoque se centra en la experiencia individual del estudiante, ya que fomenta el desarrollo de habilidades comunicativas de manera autónoma y creativa, posibilitándolo para analizar diversos contextos y enfrentarse a problemas del mundo real. Cabe destacar que los textos revisados identifican varios ejes temáticos comunes con cambios perceptibles en la instauración de estas pedagogías, destacando la innovación, la inclusión y la resiliencia como aspectos fundamentales en el campo educativo.
Keywords: Pedagogías emergentes, era digital, educación, innovación, inclusión.